Designing a Mixed Reality Extension for an Educational Board Game on Fractions - Marfisi-Schottman, Iza; Touel, Sofiane; George, Sébastien (International Journal of Virtual Reality, 2021)
Fractions are one of the most complex and challenging notions for children and can often lead to frustration and a revulsion for mathematics in general. In this article, we present the Magic Cauldron, a Mixed Reality (MR) application, designed to help children apprehend fractions in a fun and interactive way. The proposed solution is a digital extension to a board game, called the Potion Workshop that is used to introduce fractions in more than 2000 schools in France. We put together a team, composed of the mathematics didacticians who designed the Potion Workshop, several teachers who use this game in their class, a multimedia designer and computer scientists, in order to create a MR game that would tackle several of the key notions that are still hard to grasp. In this article, we present the Design-Based method followed by this team. It offers insights on how to implicate non-computer scientists in the design of complex custom MR interactions. Through several cycles of collaborative design, involving three teachers and their students and the development of three prototypes, this method allowed us to produce a truly original MR application.